2011
DOI: 10.1080/10810730.2010.529495
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interpersonal Communication in Preventing Unsafe Abortion in Communities: The Dialogues for Life Project in Nepal

Abstract: Legal, procedural, and institutional restrictions on safe abortion services—such as laws forbidding the practice or policies preventing donors from supporting groups who provide legal services—remain a major access barrier for women worldwide. However, even when abortion services are legal, women face social and cultural barriers to accessing safe abortion services and preventing unwanted pregnancy. Interpersonal communication interventions play an important role in overcoming these obstacles, including as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Furthermore, Nepal is primarily a maledominant country. When it comes to deciding on contraceptive methods, number, and gender of children; husbands have a greater decision making authority than the wives (Bhattaria, 2011). Thus, it is vital for both male and female students to be a part of prolife education so that they can make an informed decision about their reproductive health and family.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Nepal is primarily a maledominant country. When it comes to deciding on contraceptive methods, number, and gender of children; husbands have a greater decision making authority than the wives (Bhattaria, 2011). Thus, it is vital for both male and female students to be a part of prolife education so that they can make an informed decision about their reproductive health and family.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, a study showed that 36% of women between 25 and 29 years of age seek induced abortion (Thapa & Padhye, 2001). In Nepal, common reasons for seeking induced abortion are multiple pregnancies (61.4%), completed desired family size (61.4%), unwanted pregnancy in marriage (10.52%), unintended pregnancy in unmarried young women (5.26%) and a desire to have a son instead of a daughter (Puri et al, 2007;Dawadi & Shrestha, 2007;Shrivastava, Bajracharya & Thapa, 2010& Bhattarai, 2011.…”
Section: Significance Of Problem the Prevalence Of Induced Abortion mentioning
confidence: 99%
See 2 more Smart Citations
“…Most abortions (89%) are performed early in pregnancy, before nine weeks [2]. In the USA, women seek abortion for reasons related to their circumstances, such as socioeconomic aspects, age, health, parity, and marital status [3]: these reasons are similar for women and men in a Nordic context [4,5], especially for women and men involved in repeat abortion [6,7]. Men's role in sexual and reproductive health is not always clear.…”
Section: Introductionmentioning
confidence: 99%